Correction: Assessing the effects of mining projects on child health in sub-Saharan Africa: a multi-country analysis - Hermínio Cossa; Dominik Dietler; Eusébio Macete; Khátia Munguambe; Mirko S. Winkler; Günther Fink (BMC, 2022)
An amendment to this paper has been published and can be accessed via the original article.